2020
DOI: 10.3390/medicina56070348
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Everolimus and Radiation Therapy on Pulmonary Fibrosis

Abstract: Background and objectives: Everolimus (EVE) is a mammalian target of the rapamycin (mTOR) inhibitor that is widely used in cancer patients. Pulmonary toxicity, usually manifesting as interstitial pneumonitis, is a serious adverse effect of this drug. Radiation therapy, which is often administered in conjunction with chemotherapy for synergistic effects, also causes pulmonary fibrosis. In view of pulmonary damage development in these two forms of cancer treatment, we have examined the effect of EVE administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…Recently, due to its immunosuppressive effect, EVR has garnered much greater attention as a molecular targeting drug ( 18 ). Meanwhile, EVR has anti-pulmonary fibrosis, anti-renal fibrosis, anti-arthrofibrosis, and anti-hepatic fibrosis therapeutic potential in addition to its widespread use in traditional anti-cancer therapies ( 21 , 29 , 30 ). However, overall safety data for EVR in CAD patients, obtained from controlled research with the CsA group, revealed that EVR was superior to measured glomerular filtration rate (mGFR), but was associated with more adverse events ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, due to its immunosuppressive effect, EVR has garnered much greater attention as a molecular targeting drug ( 18 ). Meanwhile, EVR has anti-pulmonary fibrosis, anti-renal fibrosis, anti-arthrofibrosis, and anti-hepatic fibrosis therapeutic potential in addition to its widespread use in traditional anti-cancer therapies ( 21 , 29 , 30 ). However, overall safety data for EVR in CAD patients, obtained from controlled research with the CsA group, revealed that EVR was superior to measured glomerular filtration rate (mGFR), but was associated with more adverse events ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest research, it has been reported that EVR attenuates tacrolimus-induced renal interstitial fibrosis in rats through suppressed TGF-β1 production ( 20 ). However, one research demonstrated that EVR led to serious pulmonary fibrosis and interstitial pneumonitis after administration in some cancer patients ( 21 ). Similarly, EVR also has the double face during the progression of EMT and fibrosis in in hepatic stellate cell and human liver cancer cells ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de a cirurgia oncológica ser o procedimento que gera mais danos na função pulmonar quando comparada aos outros 33 , sabe-se que a radioterapia também tem efeitos deletérios sobre a funcionalidade respiratória, estando relacionada principalmente à dosagem e local de incidência 26 . Essas repercussões se dão pelo desenvolvimento de pneumonite actínica e fibrose pulmonar, que se manifestam de modo agudo e tardio, respectivamente 10 . Dessa forma, ressalta-se que fatores como a heterogeneidade dos pacientes no que diz respeito à realização de outro procedimento terapêutico prévio, como a própria radioterapia ou quimioterapia anterior, podem ter influenciado nos resultados obtidos na avaliação pulmonar desta amostra.…”
Section: Discussionunclassified
“…Apesar dos avanços no tratamento e sobrevida de pacientes com neoplasias 6 , a quimioterapia, apresenta complicações conhecidas e efeito adversos comuns como reações alérgicas, dor, fadiga e nauséas 7,8 . Porém, alguns medicamentos promovem um estresse oxidativo que contribuem para respostas inflamatórias e consequente fibrose pulmonar e toxicidade do organismo 9 , além de afetar diretamente na nutrição dos indivíduos, diminuindo assim a sua qualidade de vida e o seu bem-estar durante o tratamento 10,11 .…”
Section: Introductionunclassified